2015
DOI: 10.1186/s12864-015-2016-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of QTL and genomic prediction using allele-specific expression SNPs demonstrates that the complex trait of genetic resistance to Marek’s disease is predominantly determined by transcriptional regulation

Abstract: BackgroundMarek’s disease (MD) is a lymphoproliferative disease of poultry induced by Marek’s disease virus (MDV), a highly oncogenic alphaherpesvirus. Identifying the underlying genes conferring MD genetic resistance is desired for more efficacious control measures including genomic selection, which requires accurately identified genetic markers throughout the chicken genome.MethodsHypothesizing that variants located in transcriptional regulatory regions are the main mechanism underlying this complex trait, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Even though broilers and layers showed substantial differences in enriched pathways after Marek virus infection, toll-like receptor and janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling pathways were activated in both the genotypes when responding to the infection [ 117 ]. It has also been reported that 1,824 allele-specific expression SNP account for more than 83% of the genetic variance in resistance against MD in an experimental inbred layer population [ 118 ]. According to these results, the genetic merit of 200 rosters was predicted only using the allele-specific expression SNP and a progeny test was carried out.…”
Section: Disease Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Even though broilers and layers showed substantial differences in enriched pathways after Marek virus infection, toll-like receptor and janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling pathways were activated in both the genotypes when responding to the infection [ 117 ]. It has also been reported that 1,824 allele-specific expression SNP account for more than 83% of the genetic variance in resistance against MD in an experimental inbred layer population [ 118 ]. According to these results, the genetic merit of 200 rosters was predicted only using the allele-specific expression SNP and a progeny test was carried out.…”
Section: Disease Resistancementioning
confidence: 99%
“…The progeny showed a reduction of 22% in the incidence of MD after only one generation of bidirectional selection based on those SNP. Moreover, the accuracy of the estimated breeding value was increased by 125% using the allele-specific expression SNP compared to the traditional pedigree-based method [ 118 ]. In order to better understand the genetic basis of the resistance against MD, other brilliant genome-wide [ 119 , 120 ] and transcriptomic [ 121 , 122 ] studies have been performed.…”
Section: Disease Resistancementioning
confidence: 99%
“…For example, Avian Disease and Oncology Laboratory (ADOL) experimental inbred lines 6 3 and 7 2 chickens share the same MHC haplotype, yet differ greatly in resistance to MD. As these non-MHC loci are smaller in genetic effect, identifying them has been more challenging though recent efforts based on allele-specific expression in response to MDV challenge have been able to identify a large collection that accounts for over 80% of the genetic variance [Cheng et al, 2015].…”
mentioning
confidence: 99%
“…They use the publicly available unlabeled sets to enrich the training data of the classifiers using self-learning and co-training to combine both miRNA and gene expression sets. Other techniques were proposed that perform mapping between different biological features, as [9,10].…”
Section: Related Workmentioning
confidence: 99%